2023
DOI: 10.1186/s12889-023-17403-y
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of psychological resilience between social support and anxiety/depression in people living with HIV/AIDS–a study from China

Yongbing Sun,
Bing Song,
Cheng Zhen
et al.

Abstract: Objective To understand the relationship between psychological resilience in social support and anxiety/depression in people living with HIV/AIDS and to verify whether there is a mediating effect. Methods The questionnaire was administered to 161 people living with HIV/AIDS in a hospital. The questionnaire contained a general questionnaire, the Hospital Anxiety and Depression Scale (HADS), the Psychological Resilience Inventory (CD-RICS), and the Social Collaborative Support Scale (PSSS), and Pearson correlati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Sun et al . [ 43 ] used acquired immunodeficiency syndrome (AIDS) patients as study subjects and found that depression was negatively correlated with psychological resilience. Wu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al . [ 43 ] used acquired immunodeficiency syndrome (AIDS) patients as study subjects and found that depression was negatively correlated with psychological resilience. Wu et al .…”
Section: Discussionmentioning
confidence: 99%